Development of Adversity Quotient (AQ) index of pre-service teachers in Institute of Teacher Education (IPG) - Mohd Adnan, Rafidah; Mohd Matore, Mohd Effendi Ewan (Frontiers in Public Health, 2022)
The study aims to develop the Adversity Quotient (AQ) index of pre-service teachers during practicum training. The study also has assessed psychometric characteristics using the Rasch model. The original contribution is by addressing gaps of measuring AQ accurately among pre-service teachers through index at the Institute of Teacher Education (IPG) that not been widely explored. The research design entails a survey with a quantitative approach through questionnaires. The four main constructs of AQ comprises Control, Ownership, Reach, and Endurance (CORE model). This study involves several key procedures such as challenge identification, expert validity, item development, and psychometric testing of items before developing the index. A total of 96 items were produced and piloted over 159 pre-service teachers. Findings from the pilot study showed 54 items that met all assumptions from the Rasch model such as item fit, unidimensionality, local independence, reliability, and separation index. The actual study was conducted on 542 pre-service teachers from five Malaysian Institutes of Teacher Education (IPG) in the Central Zone through stratified random sampling. The data were analyzed using SPSS version 26.0 and WINSTEPS version 3.71.0.1. The findings showed the 46.86% of practicum pre-service teachers have a moderately high AQ index with 74.80. The Control and Ownership recorded a high level AQ index with 77.30 and 77.10, respectively, while Reach and Endurance were at a moderate level AQ index with 73.20 and 71.50. The AQ index of male pre-service teachers is higher (76.29) than the female (74.09). It can be seen that eighth semester pre-service teachers is higher (75.28) than the sixth semester (74.38). The Science (SN) field recorded as a highest index (80.45), while the Visual Arts Education (PSV) field has a lowest index score (70.29). Further studies can be done by reviewing the pre-service teacher development program by empowering the reach and endurance aspects to ensure that the future teachers are resilient to challenges.